Uezd Town of Menzelinsk in the Late 18th – First Half of the 19th Century - Liliya R. Gabdrafikova (Историческая этнология, 2018)
The article examines the socio-economic development and the formation of the management system in the uezd town of Menzelinsk and personalities of the city government. The demographic and the social estate composition of the population, the nature of employment of citizens, the socio-cultural sphere, and the trade turnover of the Menzelinsky Fair have been analyzed. Based on the unknown documents from the archive of the Orenburg region, the process of creating the Menzelinsk Town Hall, The paper also examines the conflict between the townspeople and mayor Nikolai Obaschikov in the 1830 and the murder case of officer Mukhametgali Alkin in Menzelinskin 1838.